Heart failure at the end of life: symptoms, function, and medical care in the Cardiovascular Health Study. - Sullivan, Mark D; O'Meara, Ellen S (Am J Geriatr Cardiol, 2006)
Among Cardiovascular Health Study participants who died from coronary heart disease, the authors compared those with incident and definite congestive heart failure (CHF) (n=60; 15%) and those with prevalent or probable CHF (n=70; 17.5%) to those with no history of CHF (n=198; 50%) concerning health status at the end of life. Both CHF groups had worse health status before death than the group without CHF. Patients in the CHF groups were more likely to use benzodiazepines (20% and 19% vs. 6%; p=0.001) and to rate their health as fair or poor (68% and 63% vs. 41%; p<0.001). They were more likely to be hospitalized (33% and 28% vs. 11%; p<0.001), to have activity restrictions (79% and 62% vs. 38%; p<0.001), and to report a wide array of physical symptoms. These data suggest that patients who die from coronary heart disease in the presence of CHF have greater need for hospice or palliative care than those with no history of CHF.
Keywords: Activities of Daily Living; Aged; Comorbidity; Coronary Disease; Female; Health Status; Heart Failure; Hospice Care; Humans; Male; Palliative Care